“It’s Helpful but Unreliable”: Exploring EFL Postgraduate Students’ Beliefs in Using ChatGPT in Academic Writing - Siregar, Renol Aprico; Lengkanawati, Nenden Sri; Damayanti, Ika Lestari (Institut Agama Islam Negeri Kudus, 2025)
Chat Generative Pre-Trained Transformer (ChatGPT) has emerged as a valuable tool for enhancing writing and other creative activities. However, there has been limited exploration of postgraduate students' perspectives on utilizing ChatGPT within the realm of academic writing. To address this gap, this study conducted semi-structured interviews with two postgraduate students from different universities to gather their narratives and experiences regarding the integration of ChatGPT into their academic writing processes. The thematic analysis reveals that the students hold a favorable view of ChatGPT's utility in aiding their academic writing, particularly in generating ideas, creating outlines, and receiving prompt feedback on their work. Nevertheless, the findings raise concerns about the validity and reliability of the information generated, particularly regarding usage limitations. The study highlights the need for more professional development programs to enhance the digital literacy of postgraduate students by utilizing artificial intelligence. Additionally, the study's contributions are detailed, along with several recommendations for future research.